Postdischarge nausea and vomiting (PDNV) in children: A review and observational study - Frelich, Michal; Vodicka, Vojtech; Jor, Ondrej; Bursa, Filip; Formanek, Martin; Sklienka, Peter; Prochazka, Vaclav (Biomedical papers, 2023)
Postdischarge nausea and vomiting (PDNV) cause substantial pediatric morbidity with potentially serious postoperative complications. However, few studies have addressed PDNV prevention and treatment in pediatric patients. Here we searched the literature and processed it in a narrative review describing PDNV incidence, risk factors, and management in pediatric patients.. A successful strategy for reducing PDNV considers both the pharmacokinetics of the antiemetic agents and the principle of multimodal prophylaxis, utilizing agents of different pharmacologic classes. Since many highly effective antiemetic agents have relatively short half-lives, a different approach must be used to prevent PDNV. A combination of oral and intravenous medications with longer half-lives, such as palonosetron or aprepitant, can be used. In addition, we designed a prospective observational study with the primary objective of determining PDNV incidence. In our study group of 205 children, the overall PDNV incidence was 14.6% (30 of 205), including 21 children suffering from nausea and 9 suffering from vomiting.
Keywords: postoperative nausea; postoperative vomiting; postdischarge nausea; postdischarge vomiting; antiemetics; setrons